Antarctic krill oil exhibited synergistic effects with nobiletin and theanine in ameliorating memory and cognitive deficiency in SAMP8 mice: Applying the perspective of the sea–land combination to retard brain aging - Wang, Cheng-Cheng; Kong, Jing-Ya; Li, Xiao-Yue; Yang, Jin-Yue; Xue, Chang-Hu; Yanagita, Teruyoshi; Wang, Yu-Ming (Frontiers in Aging Neuroscience, 2022)
The complex pathogenesis of Alzheimer's disease (AD) leads to a limited therapeutic effect; therefore, the combination of multiple bioactive ingredients may be more effective in improving AD due to synergistic effects. Based on the perspective of the sea–land combination, the effects of sea-derived Antarctic krill oil (AKO) combined with land-derived nobiletin (Nob) and L-theanine (The) on memory loss and cognitive deficiency were studied in senescence-accelerated prone 8 mice (SAMP8). The results demonstrated that AKO combined with The significantly increased the number of platform crossings in the Morris water maze test by 1.6-fold, and AKO combined with Nob significantly increased the preference index in a novel object recognition test. AKO exhibited synergistic effects with Nob and The in ameliorating recognition memory and spatial memory deficiency in SAMP8 mice, respectively. Further research of the mechanism indicated that AKO exhibited synergistic effects with Nob in suppressing β-amyloid (Aβ) aggregation, neurofibrillary tangles, and apoptosis and neuroinflammation, while the synergistic effects of AKO and The involved in synaptic plasticity and anti-neuroinflammation, which revealed that the combination was complex, not a mechanical addition. These findings revealed that the sea–land combination may be an effective strategy to treat and alleviate AD.